Relevansi Batas Usia Perkawinan dalam Membentuk Keluarga Sakinah - Suhaili, Achmad (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2018)
Marriage in Islamic view is something noble and sacred, meaning worship to Allah, follow the Sunnah of the Prophet and carried out on the basis of sincerity, responsibility, and follow the legal provisions to be heeded. In Law No. 1 of 1974 on Marriage of Chapter I, article 1, marriage is a spiritual bond between a man and a woman as a husband and wife in order to form a happy and eternal family (household) based on the One Godhead. Whereas the purpose of marriage is as God says s.w.t. in the letter of Ar-Rum verse 21